Ionic liquid based on imidazolium cation to modify functional materials on separation of active compounds. Issue 15 (2nd October 2018) - Li, Guizhen; Ho Row, Kyung
Abstract: Ionic liquids with imidazolium as cation are usually synthesized with different types of imidazolium cations, substituents, and anions. This review mainly focuses on of imidazolium-based ionic liquids in the field of modifying functional materials applied on separation of active compounds, especially on chromatographic separations ((high performance liquid chromatography (HPLC) and gas chromatograph (GC)) using materials based on imidazolium functionality as stationary phase. In addition, the preparation, classification, and physicochemical properties of various types of imidazolium-based ionic liquids are described. Although further studies are still much required, applications of imidazolium-based ionic liquids processes has made great progress in recent years and provided a new perspective in many fields. The problems associated with the industrial use of imidazolium-based ionic liquids are still required to further dealt with. Graphical Abstract: